2021
DOI: 10.3390/antiox10040513
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Effects of Tracheloside on Colorectal Cancer Cell Proliferation and Metastasis

Abstract: Recent research suggests a relationship between cancer progression and oxidative mechanisms. Among the phenolic compounds such as tracheloside (TCS) are a major bioactive compound that can combat oxidant stress-related chronic diseases and that also displays anti-tumor activity. Although TCS can inhibit mammalian carcinoma, its effects on colorectal cancer (CRC) have not been clarified. The purpose of this study was to investigate the effects of TCS on the proliferation of CRC cells, the metastasis of CT26 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…In addition, prior to determining the anti-CRC activity of the candidates in the CT 26 allograft model of CRC (a widely used animal model for cancer drug development that allows for quick and cost-effective experimental testing of potential drugs), the anti-proliferative activity of the CFSs of 21 candidates was examined against CT 26 cells in vitro . Previous reports have shown that the level of anti-proliferative activity differs depending on the cell line ( Savic et al, 2020 ; Shin et al, 2021 ); thus, some of the CFSs exerted no or little anti-proliferative activity against CT 26 cells. Of the 21 candidates, the CFS of GM07 exerted the highest anti-proliferative effect against CT 26 cells; hence, GM07 was chosen for further investigation and the generative gut microbe was identified as O. splanchnicus through phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, prior to determining the anti-CRC activity of the candidates in the CT 26 allograft model of CRC (a widely used animal model for cancer drug development that allows for quick and cost-effective experimental testing of potential drugs), the anti-proliferative activity of the CFSs of 21 candidates was examined against CT 26 cells in vitro . Previous reports have shown that the level of anti-proliferative activity differs depending on the cell line ( Savic et al, 2020 ; Shin et al, 2021 ); thus, some of the CFSs exerted no or little anti-proliferative activity against CT 26 cells. Of the 21 candidates, the CFS of GM07 exerted the highest anti-proliferative effect against CT 26 cells; hence, GM07 was chosen for further investigation and the generative gut microbe was identified as O. splanchnicus through phylogenetic analysis.…”
Section: Discussionmentioning
confidence: 98%
“… 96 Some other natural products, like Tracheloside (TCS) and Deoxypodophyllotoxin (DPT), could significantly inhibit the growth of CRC cells. 97 , 98 …”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…The mouse colon cancer (CT-26) cells were grown in Dulbecco’s Modified Eagle Medium (DMEM) with 10% fetal bovine serum and 1% antibiotic at 37 °C in a humidified incubator with 5% CO 2 [ 26 ].…”
Section: Methodsmentioning
confidence: 99%